Lossless single-molecule counting to absolute quantify proteoforms - Tobias Gross; Tobias Hundertmark; Villő Csiszár; András Attila Sulyok; Nina Gross; Maike Breiden; Niklas Kitschen; Uritza von Groll; Christoph Niemöller; Pablo Sánchez-Martín; Anne Heine; Jens Göpfert; et al. (Scientific Reports)
Abstract A novel immunoassay, termed Protein Interaction Coupling (PICO), is introduced to deliver clear, reference-free quantification of proteoforms - precise quantification. PICO employs a compartmentalized, homogeneous single-molecule assay with lossless and sensitive signal generation, capable of detecting down to a few molecules per reaction. Additionally, it utilizes a background-free, digital enumeration principle, known as decouplexing. PICO is presented as mathematical theories, providing a theoretical understanding of its chemistry. Consequently, PICO demonstrates precise quantification, as exemplified with recombinant and non-recombinant ErbB2 and multi-tagged peptide rTRX targets, validating quantification against internal and external references in both analytical and cellular matrices. Furthermore, PICO enables combinatorial multiplexing (cplex), a readout between any two antibodies, demonstrated by an 8-plex antibody, 12-cplex PICO, measuring functional changes of the ErbB pathway upon mock and dactolisib treatment delivering quantitative cellular stoichiometry. PICO possesses significant potential for versatile, standardized, and accurate protein measurements, offering insights into physiological and perturbed cellular processes.